Scalable routing strategies for ad hoc wireless networks. - Iwata, A. (IEEE Journal on selected areas in communications)
We consider a large population of mobile stations that are interconnected by a multihop wireless network. The applications of this wireless infrastructure range from ad hoc networking (e.g., collaborative, distributed computing) to disaster recovery (e.g., fire, flood, earthquake), law enforcement (e.g., crowd control, search-and-rescue), and military (automated battlefield). Key characteristics of this system are the large number of users, their mobility, and the need to operate without the support of a fixed (wired or wireless) infrastructure. The last feature sets this system apart from existing cellular systems and in fact makes its design much more challenging. In this environment, we investigate routing strategies that scale well to large populations and can handle mobility. In addition, we address the need to support multimedia communications, with low latency requirements for interactive traffic and quality-of-service (QoS) support for real-time streams (voice/video). In the wireless routing area, several schemes have already been proposed and implemented (e.g., hierarchical routing, on-demand routing, etc.). We introduce two new schemes-fisheye state routing (FSR) and hierarchical state routing (HSR)-which offer some competitive advantages over the existing schemes. We compare the performance of existing and proposed schemes via simulation